Perceptions of Organizational Politics and Job Satisfaction in Nepali Manufacturing and Information Technology Industries - Pokhrel, Shree Krishna; Goyal, Ritu; Karki, Hitesh (JMC Research Journal, 2021)
The study examines the relationship between perceptions of organizational politics (POP) and employee job satisfaction (JS) in manufacturing and information technology based organizations of Nepal. The study assesses a major hypothesis along with seven sub-hypotheses. Data is collected using convenience sampling from one hundred three employees. Correlation and regression are performed for data analysis. The study found that perceived organizational politics and job satisfaction have a significant negative relationship among employees of manufacturing and information technology based organizations.